Design and Construction of a Portable and Real-Time Monitoring System Based on the Internet of Things (IoT) for CO2 Gas Leaks - Novia Masni Dwi Putri; Abdul Muid; Nina Siti Aminah; Irfan Dwi Aditya (Departement of Physics Faculty of Mathematics and Natural Sciences, and Institute of Research and Community Services Udayana University, Kampus Bukit Jimbaran Badung Bali, 2026)
Carbon dioxide (CO₂) is the second most abundant contributor to the greenhouse effect after water vapor. Its atmospheric concentration has continued to rise over the past decade, correlating with the increase in global average temperature. Carbon Capture and Storage (CCS) is a technological approach designed to reduce CO₂ emissions by capturing CO₂ from industrial sources, transporting it to designated sites, and storing it securely. Continuous monitoring of CO₂ levels plays a critical role in CCS operations to ensure that stored CO₂ does not leak back into the atmosphere. This study presents a portable, real-time monitoring system for detecting CO₂ leakage using an MG-811 sensor integrated with an Internet of Things (IoT) platform. The system utilizes long-range communication networks for data transmission, enabling real-time visualization and analysis. In contrast to previous research, the proposed system not only displays concentration data but also includes an early warning feature and user-friendly visualization. It is powered by solar energy, allowing autonomous operation in remote areas.The results demonstrate that the sensor responds effectively to variations in gas concentration and environmental parameters. The system provides leakage vulnerability alerts using three categories: SAFE, ALERT, and DANGER. This approach enables faster identification of potential CO₂ leakage, supporting earlier and more effective mitigation actions.